The burnout phenomenon: changes in psychosocial profiles of secondary school teachers - Roslan, Samsilah; Md Nor, Sharifah; Thirumalai, Vetha Nayagy (Universiti Putra Malaysia Press, 2012)
In Malaysia, apart from teaching, teachers are burdened by clerical and administrative works as well. This phenomenon requires them to constantly learn new skills, take good care of their students’ well-being and mediate the school and the community. The present study investigated the secondary school teachers’ psychosocial profiles, such as (a) commitments, (b) motivation (c) self-confidence, (d) efficiency, (e) competence, and (f) social skills. Other influencing factors being studied were: (a) work load, (b) work conditions, and (c) burnout. A total of 304 teachers from 16 schools, inclusive of rural and urban schools, as well as at-risk and normal schools were involved in the study. A self-report survey was developed by the researchers to be administered to the respondents and to collect the research data. Five dimensions of teachers’ psychosocial profile and one aspect of teachers’ perception towards change in working conditions were studied using items measured in a 5-point scale, except for burnout which was measured using a 4-point scale. Reliability of items measured was obtained using Cronbach’s alpha. In general, the findings revealed that there were changes in the teachers’ psychosocial aspects that should be taken seriously and their burnout levels have increased significantly over the years, i.e. from 1.7713 (SD=1.7713) to 1.9387 (SD=1.9387) (df=299, t=6.39, p<.05). Thus, it was suggested that teachers need support from all quarters to ensure a positive change in their psychosocial profiles.